Functional and Evolutionary Characterization of a Gene Transfer Agent's Multilocus "Genome". (24th June 2016) - Hynes, Alexander P.; Shakya, Migun; Mercer, Ryan G.; Grüll, Marc P.; Bown, Luke; Davidson, Fraser; Steffen, Ekaterina; Matchem, Heidi; Peach, Mandy E.; Berger, Tim; Grebe, Katherine; Zhaxybayeva, Olga; et al.
Abstract: Gene transfer agents (GTAs) are phage-like particles that can package and transfer a random piece of the producing cell's genome, but are unable to transfer all the genes required for their own production. As such, GTAs represent an evolutionary conundrum: are they selfish genetic elements propagating through an unknown mechanism, defective viruses, or viral structures "repurposed" by cells for gene exchange, as their name implies? In Rhodobacter capsulatus, production of the R. capsulatus GTA (RcGTA) particles is associated with a cluster of genes resembling a small prophage. Utilizing transcriptomic, genetic and biochemical approaches, we report that the RcGTA "genome" consists of at least 24 genes distributed across five distinct loci. We demonstrate that, of these additional loci, two are involved in cell recognition and binding and one in the production and maturation of RcGTA particles. The five RcGTA "genome" loci are widespread within Rhodobacterales, but not all loci have the same evolutionary histories. Specifically, two of the loci have been subject to frequent, probably virus-mediated, gene transfer events. We argue that it is unlikely that RcGTA is a selfish genetic element. Instead, our findings are compatible with the scenario that RcGTA is a virus-derived element maintained by the producing organism due to a selective advantage of within-population gene exchange. The modularity of the RcGTA "genome" is presumably a result of selection on the host organism to retain GTA functionality.